PERAN MASYARAKAT DESA SENAKIN DALAM PENGELOLAAN WISATA RIAM SOLAKNG SEBAGAI KAWASAN WISATA ALAM DI KECAMATAN SENGAH TEMILA KABUPATEN LANDAK - Dimas, Ignasius; Fahrizal, M; AM, Iskandar (Universitas Tanjungpura, 2017)
Ecotourism is a trip that is responsible to the preservation of natural areas and can provide benefits for the economy and maintain cultural integrity. This research aims to find out the role of the Senakin Village community in the management of Solakng Rapids, the obstacles in its management and the strategies of managing the Solakng Rapids. The methods used were survey, in-depth interview, questionnaire, observation and documentation, so purposive sampling was used and analyzed with descriptive qualitative approach. The results of the study showed that the community is more competent in managing the tourist attraction of Solakng Rapids through conserving natural resources and protecting cultural values. The constraints of the community in the management of the tourist attraction of Solakng Rapids are there is still doubt among the local community due to the lack of cooperation with the institutions concerned. Meanwhile, the management strategies of Solakng Rapids are unknown as the status of ownership is unknown, while the Senakin village development planning is set in the Village Medium Term Development Plan. Keywords: Ecotourism, Management, Role of the Community, Solakng Rapids